Clinical, functional and neuropsychological status of joint replacement patients - Akhsarbek H. Dzhigkaev; Anastasia M. Tynterova; Ivan I. Kozenkov; Eldar V. Khaibulin; Elena V. Trofimova; Konstantin Y. Popadin; Konstantin V. Gunbin; Andrey G. Goncharov (Гений oртопедии)
Introduction The number of hip and knee replacement surgeries is increasing annually in Russia and worldwide. The majority of patients receiving joint arthroplasties are elderly women. The objective was to assess the clinical, functional and neuropsychological status of patients undergoing total knee or hip replacement. Material and methods The study included 448 patients admitted for elective surgery of total knee or hip replacement at the Department of Traumatology and Orthopedics of the Federal Center for High Medical Technologies (CHMT, Kaliningrad Region). Anthropometric parameters of the patients were measured, the medical history and concomitant diseases recorded. Common blood count and biochemistry test were evaluated preoperatively. Neuropsychological examination included assessment of cognitive and executive functions, levels of distress, depression, anxiety and somatization. Results Almost all patients studied were found to have varying degrees of obesity. A typical combination of concomitant pathology in volunteers was stage 2 hypertension, risk degree 2–3, and chronic gastritis in remission. Half of the volunteers showed moderate and high levels of distress, depression, anxiety and somatization. A significant number of volunteers showed moderate to high levels of cognitive decline. Age- and sex-related blood counts were slightly different from the normal ranges for a CBC and biochemistry. Changes in leukocyte count were detected. Discussion Leukocyte counts indicated the osteoarthritis induced inflammatory process in most patients. Mitochondrial dysfunction and aging of the immune system contributed to the “proinflammatory status.” The high rate of cognitive impairment in volunteers was associated with age and comorbidity, cardiovascular conditions, in particular. Distress and anxiety were associated with emotional reactions to surgery. Conclusion The factors reported can affect the duration and course of rehabilitation. The “pro-inflammatory status” of patients can complicate the healing of a postoperative wound. Neuropsychological disorders noted during postoperative rehabilitation can have a significant impact on physical recovery, social and professional adaptation.